Farmacobotânica, atividade antiinflamatória e parâmetros bioquímicos de Nopalea cochenillifera (L.) Salm-Dick (Cactaceae) - Necchi, Raquel Medina Martins (2011)
The family Cactaceae comprises about 1900 species in 125 genera. Nopalea cochenillifera (L.) Salm-Dyck occurs from Mexico to Panama and has been adapted in several countries. It is a shrubby plant that reaches 3-4 m tall, has cylindrical trunk and cladodes that are flat and fleshy. This species is known by names such as palma doce, palma-muida, nopal and nopalitos. It is used in traditional medicine as anti-inflammatory, analgesic, antimicrobial and diuretic. The cladodes of N. cochenillifera are present flavonoids, saponins, tannins and anthraquinones, and highlighted the occurrence of -sitosterol. Pharmacobotanical study shows that N. cochenillifera presents phylloclades with areolae composed of three straight and hyaline spines. The uniseriate epidermis has parallelociytic stomata and mucilage cells, followed by an annular collenchyma and parenchyma palisade, on average, with eight layers of cells. The vascular region consists of isolated bundles of the open colateral type, and the central cylinder, consists of a parenchyma medulla. The structures of mucilage and calcium oxalate druzes occur both in the cortical region as in the central cylinder and are more numerous near the vascular bundles, and the druze also occur in the first layer of collenchyma. These morphoanathomical characteristics, when taken together, are consistent in botanical modelo of control of quality of this plant species. The evaluation of anti-inflammatory activity of N. cochenillifera in induction of granulomatous tissue shows that animals treated with ethanol extract shows 53.5% inhibition of the formation of granulomatous tissue, while those treated with nimesulide has 58.5%, confirming significant antiinflammatory activity. With the same animals was performed the serum AST, ALT, albumin, creatinine and urea, which showed a lack of renal toxicity and suggest liver toxicity.